Improving oral and dental health through counseling, video and phantom demonstration during the Covid-19 pandemic to the Medan Belawan community - Boel, Trelia; M. Zulkarnain; Nasution, Rini Octavia; Nainggolan, Lydia Irani; Kartika, Dewi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on Basic Health Research, dental and oral diseases still occur in the province of North Sumatra, both urban and rural. Through the USU Community Service Institute, community service activities are carried out with the title of improving oral and dental health through counseling and maintenance of oral health in the Medan Belawan community. This activity is based on the need to maintain oral and dental health from an early age, so that good behavior in maintaining health can be accustomed from a young age. Implementation of counseling on Improving Dental and Oral Health during the Covid-19 Pandemic to the Medan Belawan community, totaling 67 people, activities are carried out within 1 (one) day. Extension methods and techniques include video screenings, lectures, demonstrations of phantoms in oral and dental care and question and answer sessions. The results achieved are that it is necessary to carry out further dedication to the school environment in Medan Belawan for Health Education and Maintenance during the Covid-19 Pandemic.